Redemption through Martyrdom: Depiction of Christ Hero Archetype in Eliot’s “Murder in the Cathedral” - Gautam, Sushil; Chhetry, Tek Bahadur (Nepal Journal of Multidisciplinary Research, 2021)
Mythology began as a way to answer questions about life, explain tradition, build culture and enlighten people. It tries to clarify the role of gods in human life. Mythology has multidisciplinary role as it amuses, connects history and conveys man’s relationship to god and the universe. In literature, heroes are vital and the most convincing characters as they are the icons who leave a valuable lesson to the humanity. It was Homer who first established the hero and journey archetypes approximately 800 B.C. and different authors follow the trend of using them in their work of art. Heroes set an example for entire humanity and teach the readers that there are more important things in life than personal benefits as Northrop Frye mentions in his “Myth and Metaphor”, “hero goes out to accomplish something” (213). Hero simply does not go out for adventurous journey but is on a quest, to explore the meaning of human situation and the universal values of good and evil. The main purpose of hero is to serve humanity putting his own life at risk. Joseph Campbell in his “Power of Myth” states “the ultimate aim of the hero’s quest must be neither release nor ecstasy for oneself, but the wisdom and power to serve others” (XIV). In need Christ hero archetype embraces martyrdom for the enlightenment of entire humanity. The research paper depicts the literary archetype of the Christ hero who undergoes challenges, struggles all the way and sacrifices own life for the salvation of humanity. Thomas Becket’s martyrdom in the play is the landmark for the purification of all sins of the people listing him as the Christ figure.